Caring Together the Health Action Plan for NSW. - NSW Health ([North Ryde, N.S.W.] : NSW Dept. of Health, 2009)
"Caring Together: The Health Action Plan for NSW website. Caring Together provides the NSW Government's response to the recommendations made by Mr Peter Garling SC following his Inquiry into acute care services in NSW public hospitals".
Caption title.
Title from home page (viewed on 5 May 2010)
Text, graphics video and sound.
Available via World Wide Web. On 5/05/10 freely available at: http://healthactionplan.nsw.gov.au/index.php.
System requirements: Player for files in MS Powerpoint and Adobe Acrobat reader for pdf files, and Adobe Flash for video.
Selected for archiving
Keywords: Caring Together (N.S.W.); Health planning -- New South Wales; Health services administration -- New South Wales; Public health -- New South Wales